The Labour Market Impact of Covid-19: Early Evidence for a Sample of Enterprises from Southern Europe - Allan Webster; Sangeeta Khorana; Francesco Pastore (Global Labor Organization (GLO), 2021)
This study uses evidence from World Bank enterprise surveys of a sample of firms from six countries in Southern Europe. It examines the early evidence of the effects of Covid-19 on labour markets. The evidence and the analysis are provided at a time when the pandemic is still in progress. The future progress of Covid-19 and government containment measures is uncertain, and the full economic consequences will probably continue to emerge after the end of the pandemic. The full extent of the impact on labour will probably not be the first of these. Nonetheless the possibility of learning lessons from the early stages of the pandemic is sufficiently important to make the exercise valuable. The study suggests that, despite efforts to support firms and hoard labour, there is a prospect of a significant number of firm closures with a consequent loss of employment. Temporary firm closures also represent a substantial loss of labour weeks. These are partly related to a significant number of workers subject to furloughs. Both temporary closures and furloughs impose costs that will be borne by firms, workers and government. The effects of Covid-19 on firms differ across sectors. Adverse effects tend to be higher in hospitality, non-essential retail and travel. A degree of gender segregation means that these are sectors with a high proportion of female workers and, in consequence, most of the countries in the sample exhibit an early decline of the share of women in employment. That many firms lack the capacity to survive further temporary closures of a similar duration to those in the earlier stages emphasises that the support provided in the near future is of critical importance to control employment losses through permanent firm closures.
Keywords: 330